SUBMICROSCOPIC CHANGES IN PERIODONTIC TISSUES UNDER EXPERIMENTAL OPIOID ACTION WITHIN TEN WEEKS - Fik, V.B.; Paltov, Ye.V.; Kryvko, Yu.Ya. (World of Medicine and Biology, 2020)
This paper presents the results of soft periodontal tissues sub-microscopic examination under the experimental effect of an opioid analgesic within ten weeks. The study was carried out on 22 male rats of reproductive age. The animals were administered opioid analgesic in multiple ascending dose from 0.212 mg / kg to 0.283 mg / kg. At the ultrastructural level, it has been established that the prolonged action of opioid for ten weeks leads to marked heterogeneity and reorganization of the periodontal cell components against the background of the chronic inflammatory process development, which is exacerbated by sclerotic changes.